Mobilité et apprentissages informels des étudiants : quelles traces ? - Jean-François Grassin (Recherches en didactique des langues et des cultures)
This paper questions the figure of the international student in an era of globalization through the concept of mobility, conceived as a social kinetics, and whose heuristic value we postulate in order to analyze the material, relational and cultural arrangements that students during their study stay develop locally to achieve their project and learn. We propose a methodology for collecting traces of learning moments, by the students themselves, favoring the micro, the local and the immediate. We identify mobility regimes that are as many ways of constructing the posture of a temporary inhabitant, in mobility, and that allow us to better understand the commitment of students in their learning.